An improved adaptive data rate algorithm of LoRaWAN for agricultural mobile sensor nodes - Wang, Hao; Zhang, Xihai; Liao, Jianxin; Zhang, Yu; Li, Hongbo (Computers and electronics in agriculture, 2024)
•The number of packets is dynamically adjusted based on the moving speed of nodes.•Time on Air (ToA) is used as a selection criterion for modulation parameters.•Distance, moving speed and SNR are used to determine the network margin. Wireless sensor network (WSN) is an important research area in smart agriculture. As an emerging technology, LoRa is used for communication between wireless sensor nodes. When LoRa is used as a mobile terminal node (mobile robot, drone, etc.), the Quality of Service (QoS) of LoRa network will be greatly reduced, which will have an impact on the quantitative decision-making and intelligent control in the future. Therefore, a novel Adaptive Data Rate (ADR) algorithm for agricultural mobile sensor nodes is proposed in this paper. The channel condition changes are effectively sensed based on three LoRa signal characteristics of SNR, RSSI, and frequency offset. It could respond quickly to the complex and changeable radio channel environment, and configured the modulation parameters dynamically and accurately. The Mobile LoRaSim tool and Arduino + SX1278 hardware platform were adopted for evaluation and analysis. The results showed that compared with the standard ADR algorithm and the Blind ADR algorithm, the data extraction rate of the Mobile ADR algorithm was increased by 15 %, the data collision rate was reduced by 45 %, the network energy consumption was reduced by 8 %, and the time on air was reduced by 50 %. The proposed algorithm improves the adaptability and robustness in terms of QoS of LoRaWAN networks.